Molecular phylogeny of the Austrolebias adloffi group (Cyprinodontiformes, Rivulidae), with description of two new endangered and highly endemic species of annual killifishes from the Laguna dos Patos system, southern Brazil - Volcan, Matheus Vieira; Barbosa, Crislaine; Robe, Lizandra Jaqueline; Lanés, Luis Esteban Krause (Zootaxa, 2021)
The Austrolebias adloffi species group encompasses a diverse lineage of annual killifishes that occurs along the Laguna dos Patos/Lagoa Mirim system, in both Brazilian and Uruguayan territories. We herein employ an integrative taxonomy approach to describe two new species of the group, inferring their phylogenetic relationships and evaluating their conservation status. Austrolebias cheffei sp. nov. and Austrolebias lourenciano sp. nov. are herein described from the western portion of the Laguna dos Patos system. Austrolebias cheffei is distinguished from the remaining species of the A. adloffi species group by presenting a yellowish green or yellowish blue dorsal fin, with wide black to dark brown bars extending from the base to the middle portion of the dorsal and anal fins in the males. Austrolebias lourenciano is distinguished from the remaining species of the A. adloffi species group by presenting a yellowish green dorsal fin, with light yellow or light bluish bars forming small triangles, interspersed with small dark brown rows of blotches in the dorsal fin base, and greenish blue anal fin, sometimes with lighter elongated yellowish iridescent blotches, limited to the basal region. According to mitochondrial cytb sequences, both species are reciprocally monophyletic relative to other species of the A. adloffi species group, and present positive barcoding gap values. Interestingly, both new species form a grade that is closely related to Austrolebias aff. minuano 1, an undescribed species that occurs at the opposite margin of the Laguna dos Patos. Among the other evaluated species, A. bagual, A. aff. minuano 1, A. nigrofasciatus, A. pelotapes, A. pongondo, A. arachan, and A. viarius also revealed to be reciprocally monophyletic, whereas A. minuano and A. adloffi revealed to be paraphyletic in regard to A. charrua and A. aff. minuano 2, respectively, and A. nachtigalli is subdivided in two clades, one of which including A. reicherti, which points to the need of a taxonomic review of the group. In addition, we discussed the conservation status of the new species, corrected the type locality of A. pongondo, and provided a dichotomous identification key of the A. adloffi species group.